Grinding the spent nuclear fuel simulating materials for the magnetoplasma separation - Vinnikov, D.V.; Shulgin, N.A.; Katrechko, V.V.; Yuferov, V.B.; Sokolenko, V.I.; Tkachev, V.I.; Ponomarev, A.N.; Buravilov, I.V. (Вопросы атомной науки и техники, 2016)
Consideration is given to the three methods used for the grinding of materials simulating spent nuclear fuel, in particular underwater spark discharges, the static compression and the laser sputtering. These methods were compared by measuring the sizes of obtained materials. The preference is given to the methods of static compression and the pulse laser sputtering.